TRACE ELEMENT AND SR-PB-ND-HF ISOTOPE EVIDENCE FOR ANCIENT, FLUID-DOMINATED ENRICHMENT OF THE SOURCE OF ALDAN SHIELD LAMPROITES - Davies G.R.; Stolz A.J.; Mahotkin I.L.; Nowell G.M.; Pearson D.G. (My University, 2006)
A phase of Mesozoic extension associated with the termination of continental collision at the southern margin of the Aldan Shield produced ultrabasic lamproites in a discontinuous belt 500 km long and ~150 km wide. The lamproites, locally poorly diamondiferous, were emplaced as dykes, sills and pipes. All Aldan lamproites have primitive chemical characteristics (e.g. MgO up to 22·7 wt %) and are ultrapotassic (K2O up to 8·3 wt %) and peralkaline with K2O + Na2O/Al23 in the range 0·6-1·16. A distinctive feature of these rocks is their low TiO2 content (0·5-1·4 wt %). Aldan lamproites are moderately light rare earth element (LREE) enriched with (La/Yb) N ranging from 10 to 47. Heavy rare earth element (HREE) abundances are lower than for all other lamproites by up to a factor of five. Therefore, the combined major and trace element characteristics of the Aldan samples are not typical of other lamproite occurrences. Large ion lithophile element concentrations are high (100-800 × Primitive Mantle) but the high field strength elements (HFSE; Nb, Ta, Ti) plus Th and U display unusually low concentrations for rocks of this type. The style of trace element enrichment recorded by the Aldan Shield lamproites is comparable with that of subduction-related magmatism. The Aldan lamproites have among the most extreme initial isotopic ratios yet recorded from mantle-derived magmas; εNdi= -10·3 to -22·3, 87Sr/86Sri= 0·7055-0·7079, εHfi= -7·6 to -29·4 and 206Pb/204Pbi= 16·6-17·4. When interpreted in terms of multi-stage Pb isotope evolution, the Pb isotope data require fractionation from a Bulk Earth reservoir at 3·0 Ga and subsequent evolution with second-stage μ values between 6·4 and 8·0. The inferred Archaean age of the lamproite source is consistent with Nd and Hf model ages, which range from 1·5 to 3·0 Ga. Aldan lamproites have ΔεHf values that range from +3 to -7. Trace element and Sr-Nd-Pb-Hf isotopic ratios show coherent variations that suggest that Archaean source enrichment produced the negative ΔεHf as a result of metasomatism by slab-derived hydrous melts that left rutile - garnet-bearing residua. We conclude that relatively large degrees of partial melting produced the lamproites (>5%), which explains the preservation of the isotope-trace element correlations and the low REE contents. Although high-quality trace element data (e.g. HFSE) are not available for most lamproites, it appears that many of their source regions contain a component of recycled oceanic crust, possibly including subducted sediment. The sources of the Aldan and many other lamproites are distinct from ocean island basalt mantle sources. This suggests that the long-term storage of trace element enriched lamproite sources occurred in the sub-continental lithospheric mantle and not at depth within the convecting asthenosphere. © 2006 Oxford University Press.
Keywords: FLUID ENRICHMENT; ISOTOPE GEOCHEMISTRY; POTASSIC VOLCANISM; Mesozoic; Mesozoic